(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To survey some clinical characteristics, related factors and treatment attitudes of acne patients who came for examination and treatment at Ha Dong General Hospital from January to July 2025. Methods: Cross-sectional descriptive study on 79 patients diagnosed with acne at the Dermatology Department of Ha Dong General Hospital. The study used a questionnaire to learn about clinical characteristics, related factors and treatment attitudes of patients. After collection, the data was exported to Excel files, cleaned and analyzed using Excel software. Results: The female/male incidence ratio was 1.26:1, with a mean age of 18.9 ± 5.9 years. The main types of skin lesions included blackheads (94.87%), whiteheads (88.46%) and post-inflammatory hyperpigmentation (70.51%). Regarding the severity of the disease, 57.0% of patients were classified as moderate acne. Although 58.2% of patients expressed concern about their condition, the rate of self-treatment was still high (53.2%) and the highest source of treatment information was the Internet. The survey results showed that acne is still a common dermatological disease in adolescents, affecting both sexes. Self-treatment and non-compliance with the regimen are prominent issues that need attention in clinical practice and health education communication.